From Diagnosis to Management of Oral Manifestations Associated with Crohn’s Disease: A Case Report (Asian Journal of Pharmaceutics (AJP), 2024)
In addition to the intestinal manifestations, the inflammatory bowel disease of Crohn’s disease (CD) is also associatedwith some extra-intestinal symptoms, such as ulcers in the oral cavity, which tend to aggravate the general care andcompromise the patient’s general well-being. The following case presents a 23-year-old patient with a CD complicatedby severe oral symptoms persisting despite early treatments, including recalcitrant recurrent aphthous stomatitis,mucosal swelling, and gingivitis. The patient was treated using a multidisciplinary approach that integrated bothgastroenterology and dental aspects. Systemic corticosteroids, immunosuppressive therapy, topical corticosteroids,antibacterial mouth rinses, dietary advice, and general support were among the treatment modalities provided. Thiscomprehensive plan, which significantly enhanced the patient’s quality of life, also demonstrated improvement in oralhealth and a decrease in signs and symptoms. This case demonstrates how interdisciplinary strategies can help in CDoral manifestations management, given the enhancement of the patient’s health. Further investigation and case studiesare needed to refine treatment strategies and expand understanding of these oral lesions and concerns regarding them.